Hymenoptera collections from Qatar, the United Arab Emirates and Oman. - Baker, Donald Burton (Contributions to Entomology = Beiträge zur Entomologie, 2004)
J. N. B. Brown, I. L. Hamer and C. G. Roche made important collections of Hymenoptera (Sphecoidea and Apoidea) in Qatar, the United Arab Emirates and Oman between 1979 and 1993. An annotated list of their collecting stations is provided in order to facilitate future use of their material.KeywordsPersian Gulf, biodiversity, collectors, deposition of collections.